Is SEMG recorded "hyperactivity" during mandibular rest a sign of dysfunctional jaw muscle activity and temporomandibular disorders (TMD)?. (4th July 2020) - Hu, Jianlai; Dong, Yan; Widmalm, Sven E.; Buvarp, Anders; Zhang, Tongsheng; Li, Boxiu; Lin, Min; Zhou, Dong
Abstract: Background: Some authors state that above‐normal surface electromyography (SEMG) levels during mandibular rest (MR) are a general sign of temporomandibular disorders (TMD). Objective: The  aim was to compare SEMG levels in the masseter and anterior temporalis areas during MR between patients with disc displacement (DD) and subjects identified as healthy. The  hypothesis  was that average SEMG levels would be higher in the patients during MR before and after repeated clenches with maximal effort. Methods: Thirty‐six healthy subjects, and 42 patients with DD, were included. SEMG levels were recorded bilaterally in the temporalis and masseter areas during MR before clenching and after repeated clenches with maximal effort. Multivariate analysis of variance (MANOVA) was used to compare the means of the log‐transformed SEMG‐values for the subject groups. Results: The mean MR levels in the four areas before clenching ranged from −0.19 log (µV) to 1.20 log(µV) in healthy subjects and from −0.22 log(µV) to 0.96 log(µV) in patients. The mean MR levels in the four areas after repeated clenches ranged from −0.19 log (µV) to 1.04 log(µV) in healthy subjects and from −0.27 log(µV) to 0.93 log(µV) in patients. The MANOVA test showed no significant differences in the means for MR for the four areas between the groups at the 5% significance level. Conclusion: The hypothesis that jaw muscle SEMG levels during MR are on average generally higher in TMD patients is not supported. A possible explanation for the previous findings is that activity in other muscles was mislabelled as jaw muscle activity.